PENGARUH KESUKSESAN PENYELENGGARAAN EVENT SPORT TOURISM TRIATHLON PARIAMAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA DARI TAHUN 2014 SAMPAI TAHUN 2017 - PEPY AFRILIAN (JURNAL STAMINA, 2018)
Sports tourism has become more advanced so that many sports are used as objects and attractions for tourists, one of the ways to attract tourists to sports tourism is by making sports events, with sporting events not only attracting athletes but also attracting sportsmen to come witness and give support to athletes. Pariaman is interested in introducing the beauty of the beach and its nature by organizing a Triathlon sport event. Triathlon itself is a sports branch that combines three types of sports at once, namely swimming, bicycle, and running. The implementation of the Triathlon sport event in Pariaman from 2014 to 2017 experienced ups and downs during the implementation. This study uses a descriptive method with a qualitative approach that examines the ups and downs of the success of the Pariaman Triathlon event against tourists visiting especially foreign countries.